2022
DOI: 10.1021/acs.macromol.2c00023
|View full text |Cite
|
Sign up to set email alerts
|

Facile Access to gem-Trifluoromethyl/Boron-Functionalized Polymers via Free-Radical Copolymerization and Cotelomerization

Abstract: Functional fluoropolymers are important for various applications due to the integrated characteristics of functional groups and fluorocarbon segments. Herein, we developed (1) thermally initiated and visible-light-initiated copolymerization of (trifluoromethyl)­vinyl boronic esters (CF3VBs) and unconjugated alkenes (18 examples, including vinyl ethers, esters, and amides), enabling the efficient synthesis of a broad scope of fluoropolymers in 71–92% yield and variable fractions of gem-CF3/B substituents (F CF3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The agreement of these observations with our DFT thermochemistry calculations is remarkable. We calculated the energy barrier for the addition of MVE- or NVP-based radicals to their parent monomers or to butenolides ( 1a or 2a ) and repeated the operation for the subsequent addition of the resulting radicals (Figure at the MN15/def2tzvpp/SMD=THF level of theory) . In nearly all cases, homoaddition is disfavored by 1.8–7.8 kcal/mol compared to heteroaddition, altogether supporting an alternating copolymerization mechanism.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The agreement of these observations with our DFT thermochemistry calculations is remarkable. We calculated the energy barrier for the addition of MVE- or NVP-based radicals to their parent monomers or to butenolides ( 1a or 2a ) and repeated the operation for the subsequent addition of the resulting radicals (Figure at the MN15/def2tzvpp/SMD=THF level of theory) . In nearly all cases, homoaddition is disfavored by 1.8–7.8 kcal/mol compared to heteroaddition, altogether supporting an alternating copolymerization mechanism.…”
Section: Resultsmentioning
confidence: 88%
“…The differences observed in the rate of copolymerization seem to correlate to the electron-withdrawing character of the acetal substituent, and we performed DFT calculations to support these observations (at the MN15/def2tzvpp/SMD=THF level of theory) . Considering an alternating radical copolymerization mechanism, , we were happy to find that the addition of the methyl vinyl ether (MVE) radical to a butenolide has a lower activation barrier with acetyl and benzoyl substituents than with a methoxy group and that there is a higher gain in energy as well (Figure ).…”
Section: Resultsmentioning
confidence: 92%
“…25 Very recently, Chen et al reported free-radical polymerization of gem-trifluoromethyl/boron-functionalized monomers. 26 An advantage of organoborane monomers is a closer match in reactivity ratios with St that allows for higher incorporation of hydroxyl side chain precursors in copolymers. For example, we have reported styrenic copolymers with 50, 75%, and as high as 90% incorporation of BN2VN.…”
Section: ■ Introductionmentioning
confidence: 99%
“…BN2VN’s aromaticity results in a close agreement in reactivity ratios with styrene (St) during radical polymerization ( r 1 (St) = 2.30; r 2 (BN2VN) = 0.423) and compatibility with coordination polymerization catalysts. , Organoborane oxidation under aqueous or organic conditions afforded vinyl alcohol (VA) (co)­polymers. , Ouchi and Nishikawa have described isopropenyl pinacol boronate ester (IPBpin) as an electron-rich monomer that copolymerizes with St ( r 1 (St) = 1.41; r 2 (IPBpin) = 0.085) and can be oxidatively converted to methyl vinyl alcohol residues. , In 2021, Ouchi and Nishikawa reported vinyl pinacol boronate ester (VBpin)–styrene copolymerizations ( r 1 (St) = 3.77; r 2 (VBpin) = 0.25) and postpolymerization organoborane oxidation . Very recently, Chen et al reported free-radical polymerization of gem-trifluoromethyl/boron-functionalized monomers …”
Section: Introductionmentioning
confidence: 99%
“…Considering the wide range of transformability of the boronyl group, this strategy would contribute to the versatile synthesis of end-functionalized polymers. Recently, PPM using a carbon–boron bond as the reaction site has attracted attention, and indeed many papers have been reported by some groups other than ours . The orthogonal transformation approach would open the door to syntheses of other types of inaccessible end-functionalized polymers.…”
mentioning
confidence: 99%